Developing Displayed Flipbook as Teaching Material for Assisting Teacher to Teach English in Online Learning for the Fourth Grade Elementary School Students - Ni Made Dwi Dharmayanti; I Nyoman Adi Jaya Putra; Anak Agung Gede Yudha Paramartha (Universitas Pendidikan Ganesha, 2021)
The lack of teaching materials that can facilitate students' independent learning has an impact on students' lack of understanding. In addition, the lack of teaching materials also has an impact on student learning outcomes. The purpose of this research is to create teaching materials with Flipbook. This type of research is developed using three stages, namely design, development, and evaluation. Data was collected through interviews and document analysis. There are two instruments used in this study, namely interview guidelines and expert assessment. The subject of this research is the English teacher. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results showed that the quality of the Flipbook assessed by the first expert got a score of 56. The quality assessment given by the second jury expert was 61, with a good category. The quality rating given by the user is 62, with a good category. Thus, flipbooks are categorized as suitable teaching materials. So it can be said that the flipped book teaching materials developed are feasible to be applied in the learning process. This research implies that the Flipbook developed can be used by students in an independent study.